UMPSA Researchers develop innovative mushroom cultivation product using pineapple waste - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
GAMBANG, 4 December 2023 – Pineapple plants, once considered waste in the agricultural industry, are now gaining recognition for adding value to Malaysia's agricultural sector.